Sosialisasi Bank Sampah untuk Mendukung Wisata Berkelanjutan di Kampung Batu Busuk, Kota Padang - Yega Serlina; PK Dewi Hayati; Puti Sri Komala; Warnita Warnita; Budhi Primasari; Donny Eros; Rudi Febriamansyah; Rizki Aziz (Warta Pengabdian Andalas, 2023)
Batu Busuk has an excellent opportunity to become one of the tourist areas in the eastern region of Padang City. As a tourist area, the aspects of comfort and cleanliness in the area and surroundings are essential to provide a memorable travel experience, including the residential areas nearby. Lack of public awareness of waste management and waste treatment and no application of the 3R principles of reduce, reuse and recycle are the problems encountered in Batu Busuk. The community service implementation team carried out a series of activities from 2021-2022 to support sustainable tourism development. This activity aims to increase community understanding of waste and the importance of waste management and introduce and enhance the formation of a waste bank in Batu Busuk. The activities included counselling on waste management, comparative studies and field visits to Farmers Women Group Tunas Harapan and Panca Daya waste bank, which have implemented the treatment of organic and non-organic waste into various economically valuable products. It can be concluded that waste management in Batu Busuk is needed to support sustainable tourism. A Batu Busuk Waste Bank unit is required to effectively solve the waste management problem and reduce waste generation in Batu Busuk and its tourism area. Training on the method to treat both organic waste into plant nutrients and non-organic waste into various crafts must be conducted. The products have economic value and are an effective solution for reducing the volume of waste.